2021
DOI: 10.55230/mabjournal.v49i2.1526
|View full text |Cite
|
Sign up to set email alerts
|

COMPARING THE EFFECT OF TWO COATING METHODS OF Tetragonula laeviceps PROPOLIS WATER EXTRACTION ON PHYSICAL QUALITY AND SHELF LIFE OF EGGS KEPT IN ROOM TEMPERATURE

Abstract: Studies show that in the tropical region, like Indonesia, eggs have a low shelf life, ranging from 10 to 14 days when kept at room temperature. The application of natural coating material, such as propolis, could improve the shelf life of eggs. However, due to the high cost of the material, it is necessary to find more efficient application methods. In this study, propolis extraction using aquadest as solvent was applied, by brushing and spraying, to 180 fresh eggs of local chicken (Gallus sp.) aged 24 hours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…There are studies on the application of this substance for food protection. Observation of physical and chemical characteristics of Tangerine cultivar Garut fruit showed that 10% propolis extract coating maintained endocarp firmness, diameter, and vitamin C level for also delayed the decaying process 20% longer than the control [29], another study show that 2,5% propolis extract could maintain the albumen and yolk condition up to 21 days [30]. However, most studies only applied during pre-harvest or post-harvest, and there still needs to be a report on how it affects if used during both periods.…”
Section: Introductionmentioning
confidence: 93%
“…There are studies on the application of this substance for food protection. Observation of physical and chemical characteristics of Tangerine cultivar Garut fruit showed that 10% propolis extract coating maintained endocarp firmness, diameter, and vitamin C level for also delayed the decaying process 20% longer than the control [29], another study show that 2,5% propolis extract could maintain the albumen and yolk condition up to 21 days [30]. However, most studies only applied during pre-harvest or post-harvest, and there still needs to be a report on how it affects if used during both periods.…”
Section: Introductionmentioning
confidence: 93%
“…An outstanding characteristic of propolis is the variability of its composition and multiple factors such as seasonality, climate, geographic location, and vegetation [1] [6] [7], making propolis extract production with standardized properties and their industrial exploitation quite challenging [8] [9]. In addition, the low solubility of propolis extracts in water can change the flavor and odor when incorporated into foods, leading to higher costs than conventional ingredients and making their application in foods even more strenuous [8] [10].…”
Section: Introductionmentioning
confidence: 99%